Diagnosing culture of public organization utilizing competing values framework: A mixed methods approach - Hina Rukh; Faisal Qadeer (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
Diagnosis of culture is extremely important and in great demand in literature particularly when it comes to public organizations which operate in complex and compelling social, political and economic environment. Scholars and practitioners also affirm that examining the culture of public organizations is a very complex and challenging task. It is well-known that any organizational development initiatives through a change of culture failed dramatically because the culture diagnosis is either ignored or not understood. Incidentally, in the public sector, empirical findings of the cultural diagnosis are either non-existent or sketchy. Therefore, we comprehensively diagnose the culture of a public organization by utilizing the most widely used competing values framework through sequential explanatory mixed method approach (a survey, observations and in-depth interviews). This ambitious research approach is undoubtedly very rare in diagnosing public sector organizational culture. This study accepts this challenge to make a meaningful contribution and analyses the culture concerning the competing values of flexibility/stability and internal/external relationship. Results indicated that a reliance on the hierarchy culture did exist, while managers want to depart from this bureaucratic culture and adopt the characteristics of the clan culture.
Keywords: 330; diagnosis of culture; types of culture; competing values framework; public organization